PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, DAN PORSI KEPEMILIKAN PUBLIK TERHADAP LUAS PENGUNGKAPAN SUKARELA LAPORAN TAHUNAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018) - Pirda Rianti; Ayus Ahmad Yusuf; Siti Nuke Nurfatimah (Jurnal Riset Keuangan dan Akuntansi, 2020)
This study discusses the profitability, the leverage, the size of the company and the public ownership dispersion towards the voluntary disclosure area in the basic and chemical sector manufacturing companies in the 2016-2018 period. The independent variables used are profitability, leverage, company size and the public ownership dispersion. The dependent variable is the extent of voluntary disclosure. The data analysis method in this study is a panel data regression. The study used a sample of 54 companies and 162 financial statements in 2016-2018. Data obtained based on annual report data. Data processing is performed using the Eviews 9.0 application. Evaluation result show profitability, leverage, company size and the public ownership dispersion are positive and significant to the extent of voluntary disclosure. Simultaneously all independent variables are positive and significant to the extent of voluntary disclosure. Keywords : profitability, leverage, company size, public ownership dispersion, and voluntary disclosure